PENGARUH PENERAPAN TATA KELOLA DAN BIAYA CSR TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI - Suryawan, Diva Adhindha Triamandha; Susilandari, Caecilia Atmini (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
This research aims to analyse the effect of corporate governance and corporate social responsibility (csr) on the firm’s value with financial performance as a mediation variable. The theory used agency theory and signalling theory to explain the relation independent variabel, mediating variable and dependent variable. Firm value was measured by price to book value. The sample used mining industry and the research periode was 2020 – 2023. The data analyses used descriptive statistics and multiple linear regressions. The result shows corporate governance is insignificant to the financial performance and firm value, csr expense has a positive significant to the financial performance bu unsignificant to the firm value. Financial performance is positive and significant to the firm’s value. And financial performance cannot mediate corporate governance and csr expense to the firm’s value.